New approaches of heat fluxes determination in the workplace in situ. (June 2018) - Flimel, Marián; Dupláková, Darina
Abstract: Article describes the suggestion of measurement method of heat flux density by heat line plate application in area, specifically in workplaces. It presents description of the technical process of measuring system construction for the heat flux density measuring and the method of measured values evaluation in area. Optimization of workstation position is possible with size and direction measuring of heat fluxes in workplace. It is possible to optimize the position in so called optimum state zone of heat fluxes. Determination of heat flux density enables to qualify thermal stress and thermal comfort in workplaces and it is illustrated in examples. Highlights: Heat flux density measuring with direction determination of heat fluxes. Utilization, prototype creation, advantages and disadvantages filling of this device. Evaluation of climatic environment state in terms of heat flux density effect in area. The main principle of suggested devices is application of heat plates in area.